1999
DOI: 10.1345/aph.18224
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Extended-Interval Dosing of Omeprazole in Keeping Gastroesophageal Reflux Disease Patients Symptom Free

Abstract: The potential economic advantage of alternate-day therapy for GERD maintenance must be weighed against the potential cost of failure before it can be widely instituted. The studies presented have helped develop a clinical picture of the patients who may benefit from alternate-day therapy without risk of complications or potential increases in management costs. Bank et al., reporting on a group of patients, found that patients with Grade II-IV disease had a 61% success rate at two to eight years. Bank defined s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Of the 14 publications identified, 12 were full peer‐reviewed publications 4–9, 11–16 and two were conference abstracts 17, 18 . A review article that we had retrieved from our search 19 identified eight additional conference abstracts from five separate groups of investigators 20–27 concerning either a ‘step down’ strategy or alternate day PPI therapy for the management of GERD. Direct contact with the senior investigators from two of these groups responsible for four of the abstracts 20–23 confirmed that these studies had not been published in full and that there was no additional data available from them.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 publications identified, 12 were full peer‐reviewed publications 4–9, 11–16 and two were conference abstracts 17, 18 . A review article that we had retrieved from our search 19 identified eight additional conference abstracts from five separate groups of investigators 20–27 concerning either a ‘step down’ strategy or alternate day PPI therapy for the management of GERD. Direct contact with the senior investigators from two of these groups responsible for four of the abstracts 20–23 confirmed that these studies had not been published in full and that there was no additional data available from them.…”
Section: Resultsmentioning
confidence: 99%
“…Patients are sometimes prescribed PPI as a scheduled intermittent therapy: alternate days, every 3 days or on weekends. Studies have, however, shown them to be inferior to a continuous daily dose of PPI 13–15 . Many patients on scheduled intermittent therapy eventually take medications “on‐demand” as it is even more difficult to comply with a scheduled intermittent therapy compared to continuous daily therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have, however, shown them to be inferior to a continuous daily dose of PPI. [13][14][15] Many patients on scheduled intermittent therapy Key words gastroesophageal reflux disease, on-demand therapy, proton pump inhibitors. patient satisfaction was measured using a visual analog scale.…”
mentioning
confidence: 99%
“…Based on this information, it has been suggested that alternate-day dosing may be effective in healed patients who have already completed a full course of daily omeprazole. 1 Although several abstracts have been published regarding this concept, few published reports citing full data are available.…”
Section: Introductionmentioning
confidence: 99%